Bilateral Trade Imbalances - Alejandro Cu\~nat; Robert Zymek (Center for Economic Studies and ifo Institute (CESifo), 2019)
Bilateral trade imbalances are determined by aggregate trade imbalances, production and expenditure patterns, and trade barriers. We calibrate a dynamic many-sector trade model to match the recent sectoral trade and production shares of 40 economies and the rest of the world. Through a variance decomposition and counterfactuals, the model allows us to assess the relative importance of these determinants for the observed variation in bilateral imbalances. Large pairwise asymmetries in residual trade “wedges” are needed for the model to match the data. These account for roughly 60% of the variation, with most of the rest due to differences in production and expenditure patterns. Aggregate trade imbalances play a minor role. A counterfactual trade policy which eliminates trade-wedge asymmetries would have sizeable effects on bilateral trade patterns and welfare. However, it would leave aggregate trade balances virtually unchanged.
Keywords: F15; F20; F32; F40; F62; 330; trade imbalances; trade wedges; gravity